Respiratory Disease and Nutrition - Abdala-Valencia, Hiam (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Most complex respiratory conditions invoke interactions between genetic and environmental factors, such as smoking, pollution, and diet. There is increasing evidence that diet and nutrition are important factors, not only in disease prevention, but also in their contribution to the chronicity and heterogeneity of lung disorders. Nutrients exert potent effects on metabolism through a variety of regulatory mechanisms, resulting in local and systemic changes in metabolite levels. In this issue of Nutrients, we would like to bring together papers dealing with the topic of "Respiratory Diseases and Nutrition". We welcome manuscripts detailing human and animal studies focused on the roles of dietary and metabolic factors in the initiation and progression of respiratory diseases, including, but not limited to, chronic obstructive pulmonary disease (COPD) and asthma. In vitro studies aimed at elucidating the potential molecular mechanisms of diet-metabolic interactions are also invited. We welcome different types of manuscript submissions, including original research articles and up-to-date reviews and commentaries.